What Have Been the Impacts of World Bank CDD programs? : Operational and Research Implications - Oshima, Kaori (World Bank, Washington, DC, 2015)
Community driven development (CDD) is an approach that emphasizes community control over planning decisions and investment resources. A rigorous evaluation process helps determine CDDs effectiveness in various settings and highlights areas that need strengthening for second phase programs or new projects. This note summarizes the findings of a recently conducted study, What have been the Impacts of World Bank Community Driven Development Programs? CDD impact evaluation review and operational and research implications (Wong 2012), which synthesizes the impact evaluation results of seventeen World Bank CDD programs over the past twenty five years. The study finds that, on the whole, these projects achieved their stated goals of poverty welfare reduction, poverty targeting, and increased access to services. Evidence on governance, social capital, spillovers, and conflict impacts, however, is found to be limited and mixed.